Elevated neopterin and decreased IL-4, BDNF levels and depression in lymphoma patients receiving R-CHOP chemotherapy - Mishra, Pinki; Bhurani, Dinesh; Nidhi (Frontiers in Neurology, 2024)
Objective: Depression is the most commonly observed psychological manifestation experienced by individuals diagnosed with cancer. The purpose of the study was to investigate the association between levels of IL-4, BDNF, neopterin, and depressive symptoms in lymphoma patients receiving consecutive cycles of chemotherapy.Newly diagnosed lymphoma patients scheduled to receive R-CHOP chemotherapy were enrolled. Effects of R-CHOP on circulatory biomarkers and depressive symptoms were assessed at three-time points (baseline assessment seven days before the first dose of chemotherapy (TP1), interim assessment after the third cycle of chemotherapy (TP2), and follow-up assessment after the 6th cycle of chemotherapy (TP3).Results: Seventy lymphoma patients, with a mean age of 44.17±13.67 years, were enrolled.Patients receiving R-CHOP were found significantly increased neopterin levels between given time points TP1 vs TP2, TP1 vs TP3, and TP2 vs TP3 (p<0.001). However, IL-4 and BDNF levels significantly decreased with consecutive cycles of chemotherapy (p<0.001). On Patient Health Questionnaire assessment (PHQ-9), scores of items like loss of interest, feeling depressed , sleep problems, loss of energy , and appetite problems were found significantly affected with consecutive cycles of chemotherapy (p<0.001). The study found weak negative correlations between IL-4, BDNF, and neopterin levels and changes in PHQ-9 scores at both TP2 and TP3, suggesting a potential inverse relationship between these markers and depression symptoms. Conclusion: In conclusion, the present study suggests a potential link between elevated neopterin levels, decreased IL-4, and BDNF levels,and the presence of depression in lymphoma patients receiving R-CHOP chemotherapy. This study provides valuable insights into understanding the emotional challenges faced by cancer patients, offering information for more personalized interventions and comprehensive support approaches within the oncology setting.